Evaluation of the Platelet Indices in Patients with Subclinical Hypothyroidism - Findikli, Huseyin Avni; Tutak, Ayse Sahin (Archives of Clinical and Biomedical Research, 2018)
Objective: Both mean platelet volume (MPV) and platelet distribution width (PDW) can be used for various clinical results. The aim of this study was to establish a clinicopathological relationship by examining the thrombocyte parameters of subclinical hypothyroidism (SCH) cases. Methods: A retrospective evaluation was made of 60 female subjects as a patient (subclinical) group of 30 females and an age-matched control group of 30 females. Results: The mean age was similar in both study groups as 34.9 ± 4.9 years in the patient group and 33.8 ± 3.19 years in the control group (p>0.05). The MPV and PDW values were measured higher in the patient than control group (p< 0.05). TSH and platelet parameters, there was determined to be a correlation between MPV (r=0.259, p<0.05) and PDW (r=0.269, p<0.05). Conclusion: As a result, elevated MPV and PDW levels in patients with SCH may predispose for cardiovascular diseases.